Rational design of double salt ionic liquids as extraction solvents: Separation of thiophene/n‐octane as example. Issue 8 (14th May 2019) - Song, Zhen; Hu, Xutao; Zhou, Yageng; Zhou, Teng; Qi, Zhiwen; Sundmacher, Kai
Abstract: Although double salt ionic liquids (DSILs) offer significant advantages over classical two‐ion ionic liquids as separation solvents, relevant studies are still scarce and a systematic DSIL selection method is thus highly desirable. In this contribution, a rational method for designing DSILs as extraction solvents is proposed and exemplified by the thiophene/ n ‐octane separation. The effects of additional degrees of freedom for DSIL design (i.e., double cations and/or anions and the ion ratio) on the thermodynamic properties are first analyzed by COSMO‐RS. Then, a multilevel DSIL design method combining the prediction of infinite dilution thermodynamic properties, the estimation of physical properties, the evaluation of phase equilibrium behavior, and the experimental validation is proposed. By applying this method, [C2 MIm][OAc] x [NO3 ]1‐ x ( x = [0, 1]) and [C2 MIm][OAc] x [SCN]1‐ x ( x = [0.70, 1]) are identified as promising DSIL solvents for the thiophene/ n ‐octane separation. Correspondingly, the liquid–liquid equilibria of {DSILs + thiophene + n ‐octane} with the designed DSILs are experimentally studied.